Pengaruh Penggunaan Modal terhadap Harga Saham Pada PT Bank Mandiri Tbk - Nur Athiaturrahman, Ita; Rimawan, M (Social Science Academic, 2023)
This study aims to determine the effect of Working Capital Turnover and Cash Turnover on the stock price og Bank Mandiri Tbk which is listed on the Indonesia Stock Exchange. The population in this study is from 2003-2022. The sample technique used is purposive sampling 11 year. The results of the research show that Working Capital Turnover (X1) and Cash Turnover (X2) partially have no significant effect on stock price. Simultaneously Working Capital Turnover (X1) and Cash Turnover (X2) have no effect no stock prices.